2014
DOI: 10.1007/s13394-014-0129-4
|View full text |Cite
|
Sign up to set email alerts
|

Developing an analytic lens for investigating identity as an embedder-of-numeracy

Abstract: One of the capabilities needed for effective participation in modern society is numeracy, which is the ability to cope effectively with the mathematical demands of life. While the development of numeracy continues beyond the school years, schools nevertheless have a responsibility to provide opportunities for students to expand their numeracy expertise. In Australian schools, there is a renewed emphasis on numeracy brought about by the introduction of a new curriculum, teacher professional standards and measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
9

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 32 publications
0
28
0
9
Order By: Relevance
“…This article arises from a study in which it has been suggested that teacher identity could be used as an analytic lens to investigate ways of helping teachers to promote numeracy learning (Bennison 2015). The purpose of this…”
mentioning
confidence: 99%
“…This article arises from a study in which it has been suggested that teacher identity could be used as an analytic lens to investigate ways of helping teachers to promote numeracy learning (Bennison 2015). The purpose of this…”
mentioning
confidence: 99%
“…Bennison (2015) developed a conceptual framework for teacher identity as an embedder-of-numeracy, which includes five domains of influence: knowledge, affective, social, life history and context. Bennison suggested that researchers can use the framework to capture the complexity, situatedness, and overlapping nature of teachers' multiple identities while at the same time practically focusing on social and cognitive characteristics related to a teacher as an embedder-of-numeracy.…”
Section: Operationalising Identitymentioning
confidence: 99%
“…Investigações a respeito da identidade profissional (IP) de professores têm ganhado espaço nos cenários nacional e internacional e têm sido utilizadas como lente teórica para análise de programas de formação de professores que ensinam Matemática (PEM) (Bennison;Brown, & McNamara 2011;Brown, Heywood, Solomon, & Zagorianakos, 2013;Cyrino, 2016aCyrino, , 2016bCyrino, , 2016cGoos, 2005;Goos, & Bennison, 2008;Hossain, Mendick, & Adler, 2013;Lloyd, 2006;Losano, & Cyrino, 2017;Oliveira, 2004;Pamplona, & Carvalho, 2009;Ponte, & Chapman, 2008;Teixeira, & Cyrino, 2015;Ticknor, 2012;Van Putten, Stols, & Howie, 2014).…”
Section: Introductionunclassified